The republic of virtue how we tried to ban corruption, failed, and what we can do about it - Buckley, F. H. (New York Encounter Books, 2017)
Public corruption is the silent killer of our economy. We?ve spawned the thickest network of patronage and influence ever seen in any country, a crony capitalism in which business partners with government and transfers wealth from the poor to the rich. This is a betrayal of the Framers? vision for America, and of the Constitution they saw as an anti-corruption covenant. Most Americans get it, and this explains the otherwise improbable rise of Donald Trump and Bernie Sanders.
Includes bibliographical references (pages 205-246) and index.
Keywords: Misconduct in office--United States